Transparent inorganic filler as well as preparation method and application thereof
By forming a reducing metal layer on the surface of the carbon material, transparent inorganic fillers with high conductivity and good dispersion were prepared, which solved the problem that conductive fillers in the prior art are prone to agglomeration and cannot be applied to transparent scenes, and achieved efficient conductive effects suitable for transparent applications.
Patent Information
- Application Number
- CN202311222175.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
AI Technical Summary
In the existing flexible pressure-sensitive touch control technology, the conductive filler of the pressure strain gauge is prone to agglomeration, affecting electrical properties, and cannot be applied to transparent scenarios. The graphite conductive filler needs a high content to improve the conductive effect, but it is easy to lead to poor dispersion.
Transparent inorganic filler is prepared by mixing carbon materials (graphene oxide, reduced graphene or carbon nanotubes) with metal solution and reducing agent solution and undergoing periodic microwave irradiation to form a carbon material layer and a reduced metal layer coated thereon.
It realizes high conductivity and good dispersion of transparent inorganic fillers, avoids filler agglomeration, and is transparent, suitable for transparent application scenarios.
Smart Images

Figure CN119662050A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to a transparent inorganic filler and a preparation method and application thereof. Background Art
[0002] In recent years, the use of flexible pressure-sensitive touch technology in electronic products has become increasingly common. In flexible pressure-sensitive touch technology, pressure strain gauges are widely used because of their linear pressure output characteristics. The main conductive filler of the pressure strain gauge is a mixture of metal and conductor doping (Printed Strain Gauge, PSG). PSG has high sensitivity and a wide strain range, but the doped inorganic conductor (such as carbon powder) is easy to agglomerate, affecting the electrical properties of the sensor, and it is only black and cannot be used in transparent application scenarios. If graphite is used as a conductive filler, a higher content of graphite must be added to achieve a better conductive effect. However, a high graphite content is prone to poor dispersion and cannot be used in transparent application scenarios. Summary of the invention
[0003] In view of this, the present application proposes a method for preparing a transparent inorganic filler to prepare a transparent inorganic filler with good dispersibility and high conductivity.
[0004] In addition, it is also necessary to provide a transparent inorganic filler prepared by the preparation method, as well as a transparent conductive ink and a flexible sensor structure including the transparent inorganic filler.
[0005] An embodiment of the present application provides a method for preparing a transparent inorganic filler, comprising the following steps:
[0006] Mixing and oscillating a carbon material with deionized water to prepare a carbon material solution; wherein the carbon material includes graphene oxide, reduced graphene or carbon nanotubes;
[0007] The metal solution, the reducing agent solution and the carbon material solution are mixed and shaken to obtain a mixed solution; wherein the metal solution includes one or more of a silver nitrate solution, a tetrachloroauric acid solution, a copper sulfate solution, and a platinum chloride solution, and the reducing agent solution includes one or more of a hydrated hydrazine solution, an ammonium chloride solution, and a L-arginine solution;
[0008] The mixed solution is periodically irradiated, wherein in each period, the irradiation frequency is 2.05 GHz to 2.95 GHz, the irradiation power is 800 W to 1000 W, the irradiation time is 45 to 50 seconds, and the rest time is 8 to 10 seconds;
[0009] The irradiated mixed solution is centrifuged, washed and dried to obtain the transparent inorganic filler.
[0010] One embodiment of the present application provides a transparent inorganic filler, which includes a carbon material layer and a reduced metal layer covering the carbon material layer. The carbon material layer includes graphene oxide, reduced graphene or carbon nanotubes. The reduced metal layer includes nano-metal particles, and the nano-metal particles include one or more of gold, silver, copper and platinum.
[0011] In one embodiment, the transparent inorganic filler has a thickness of 5 nm to 10 nm.
[0012] In one embodiment, the carbon material layer has a thickness of 0.4 nm to 1 nm, and the reduced metal layer has a thickness of 2.5 nm to 4.5 nm.
[0013] In one embodiment, when the carbon material layer is graphene oxide or reduced graphene, the transparent inorganic filler is in the form of a sheet, and the length of the sheet-shaped transparent inorganic filler is 10 μm to 70 μm, and the width is 10 μm to 70 μm.
[0014] An embodiment of the present application provides a transparent conductive ink, which includes the following components in parts by weight:
[0015]
[0016] The transparent inorganic filler comprises a carbon material layer and a reduced metal layer covering the carbon material layer. The carbon material layer comprises graphene oxide, reduced graphene or carbon nanotubes. The reduced metal layer comprises nano-metal particles, and the nano-metal particles comprise one or more of gold, silver, copper and platinum.
[0017] In one embodiment, the linker comprises a copolymer of ethylene, acrylic acid, methacrylic acid or polyvinyl alcohol.
[0018] In one embodiment, the auxiliary agent includes a photoinitiator, a leveling agent and a defoaming agent.
[0019] In one embodiment, the solvent includes one or more of ethylene glycol butyl ether and aromatic hydrocarbon solvents.
[0020] One embodiment of the present application provides a flexible sensor structure, which includes a circuit substrate, the transparent conductive ink as described above, a transparent conductive film and a polyethylene terephthalate film. The circuit substrate includes a substrate layer and a circuit layer arranged on the surface of the substrate layer. The transparent conductive ink is arranged on the surface of the substrate layer and is spaced from the circuit layer. The transparent conductive film covers the transparent conductive ink and the circuit layer and electrically connects the transparent conductive ink and the circuit layer. The polyethylene terephthalate film covers the transparent conductive film.
[0021] The present application reduces nano-metal particles on the surface of a carbon material (graphene oxide, reduced graphene or carbon nanotubes) so that the surface of the carbon material is coated with a reduced metal layer. Since the free electrons in the carbon material can transfer electrons in the conjugated structure of the carbon material, the free electrons outside the nano-metal particles (reduced metal layer) can form an electron cloud for electron transfer, so that the prepared transparent inorganic filler has improved conductivity. In addition, the reduced metal layer on the surface of the transparent inorganic filler has a large cross-sectional area and a lower resistance, which further improves the conductivity of the transparent conductive ink. In addition, since the carbon material in the transparent inorganic filler contains oxygen-containing groups, the oxygen-containing groups can produce hydrogen bonds in the polymer colloid and have better dispersibility, so the transparent conductive ink of the present application is not prone to filler agglomeration problems. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The present invention provides a flow chart of a method for preparing a transparent inorganic filler according to one embodiment of the present application.
[0023] Figure 2 A cross-sectional view of a transparent inorganic filler provided in accordance with one embodiment of the present application.
[0024] Figure 3 A cross-sectional view of a transparent inorganic filler provided in another embodiment of the present application.
[0025] Figure 4 A schematic diagram of a transparent conductive ink provided in accordance with one embodiment of the present application.
[0026] Figure 5 A schematic diagram of a transparent conductive ink provided in another embodiment of the present application.
[0027] Figure 6 This is a transmission electron microscope (TEM) image of the transparent conductive ink of Example 1 of the present application.
[0028] Figure 7 This is a transmission electron microscope image of the conductive ink of comparative example 1 of the present application.
[0029] Figure 8 A cross-sectional view of a flexible sensor structure provided in one embodiment of the present application.
[0030] Main component symbols
[0031] Transparent inorganic filler 10
[0032] Carbon material layer 11
[0033] Reduction of metal layer 12
[0034] Transparent Conductive Ink 20
[0035] Polymer colloid 21
[0036] Flexible sensor structure 100
[0037] Circuit board 30
[0038] Transparent conductive film 40
[0039] Polyethylene terephthalate film 50
[0040] Covering film 60
[0041] Base material layer 31
[0042] Circuit layer 32, 33
[0043] Conductive structure 34
[0044] The following specific implementation manner will further illustrate the embodiments of the present application in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION
[0045] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the technical field of the present application. The terms used herein are only for the purpose of describing specific implementation methods and are not intended to limit the present application embodiments.
[0046] It should be noted that all directional indications in the embodiments of the present application (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0047] Here, the embodiments of the present application are described with reference to the cross-sectional views, which are schematic diagrams of the idealized embodiments (and intermediate configurations) of the present application. Thus, it is foreseeable that the shapes of the diagrams are different due to manufacturing processes and / or tolerances. Therefore, the embodiments of the present application should not be interpreted as being limited to the specific shapes of the regions illustrated here, but should include deviations in shapes such as those produced due to manufacturing. The regions shown in the figures are themselves only schematic, and their shapes are not intended to illustrate the actual shapes of the devices, and are not intended to limit the scope of the present application.
[0048] Some embodiments of the present application are described in detail below in conjunction with the accompanying drawings. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.
[0049] See also Figure 1 In a first aspect, the present application provides a method for preparing a transparent inorganic filler, which includes steps S10 to S40. It is understood that the numbering of the steps is intended to clearly describe the specific preparation method, and is not intended to limit the order of the steps.
[0050] Step S10: Mix the carbon material with deionized water and oscillate to prepare a carbon material solution. The carbon material may be graphene oxide (GO), reduced graphene (rGO) or carbon nanotube (CNT). The carbon nanotubes described in the present application are oxygen-containing functional carbon nanotubes, that is, the graphene sidewalls of the carbon nanotubes have oxygen-containing functional groups introduced. The above-mentioned carbon material has a large specific surface area. Among the conductive materials of the same volume, the conductive material with a large specific surface area has a lower resistance and a higher conductivity.
[0051] In some embodiments, 15 to 20 mg of any one of commercially available graphene oxide, reduced graphene oxide, and carbon nanotubes can be weighed, added to 20 to 30 mL of deionized water, and then ultrasonically vibrated for 30 to 60 minutes to obtain a carbon material solution. The mass of the carbon material and the volume of deionized water can be adjusted according to actual needs, and the ultrasonic time can be adjusted according to the amount of carbon material and deionized water used.
[0052] Step S20: The metal solution, the reducing agent solution and the carbon material solution are mixed and shaken to obtain a mixed solution.
[0053] The metal solution may be one or more of a silver nitrate (AgNO3) solution, a tetrachloroauric acid (H(AuCl4)) solution, a copper sulfate (CuSO4) solution, and a platinum chloride (H2PtCl6·(H2O)6) solution. The concentration of the metal solution may be 10 to 15 mM, and the amount used may be 100 to 120 mL.
[0054] The reducing agent solution may be one or more of hydrated hydrazine (N2H4·H2O) solution, ammonium chloride (NH4Cl) solution, and L-arginine solution. In the reducing agent solution, the mass of the solute may be 200-250 mg, and the volume of the solvent (deionized water) may be 100-120 mL.
[0055] In some embodiments, the metal solution, reducing agent solution and carbon material solution can be poured into a Teflon bottle and mixed, and then ultrasonically vibrated for 30 to 60 minutes to obtain a mixed solution.
[0056] Step S30: the mixed solution can be placed in a microwave oven for periodic irradiation. In each cycle, the irradiation frequency is 2.05 GHz to 2.95 GHz, the irradiation power is 800 W to 1000 W, the irradiation time is 45 to 50 seconds, and the rest time is 8 to 10 seconds.
[0057] In this embodiment, in each cycle, the irradiation frequency is 2.45 GHz, the irradiation power is 900 W, the irradiation time is 50 seconds, the stop time is 10 seconds, and the number of cycles is three times (that is, irradiate for 50 seconds and then stop irradiating and maintain for 10 seconds, irradiate for 50 seconds and then stop irradiating and maintain for 10 seconds, irradiate for 50 seconds and then stop irradiating and maintain for 10 seconds, and end).
[0058] Step S40: centrifuging the irradiated mixed solution (collecting the precipitate), washing (the precipitate can be washed with deionized water for multiple times), and drying to obtain the transparent inorganic filler.
[0059] The preparation method of the present application reduces nano-metal particles on the surface of a carbon material (graphene oxide, reduced graphene or carbon nanotubes) so that the surface of the carbon material is coated with a reduced metal layer. Since the free electrons in the carbon material can transfer electrons in the conjugated structure of the carbon material, the free electrons outside the nano-metal particles (reduced metal layer) can form an electron cloud for electron transfer, so that the prepared transparent inorganic filler has an improved conductivity.
[0060] See also Figure 2 and Figure 3 In a second aspect, the present application provides a transparent inorganic filler 10 prepared by the above-mentioned preparation method, which includes a carbon material layer 11 and a reducing metal layer 12 covering the carbon material layer 11. When the carbon material layer 11 is in a sheet shape, the reducing metal layer 12 covers the six surfaces of the sheet-shaped carbon material layer 11. When the carbon material layer is in a tubular shape, the reducing metal layer 12 covers the inner wall and the outer wall of the tubular carbon material layer 11.
[0061] The carbon material layer 11 can be any one of graphene oxide (GO, flake), reduced graphene (rGO, flake) or carbon nanotube (CNT, tubular). The carbon nanotube described in the present application is an oxygen-containing functional carbon nanotube, that is, the graphene sidewall of the carbon nanotube has introduced an oxygen-containing functional group. The above-mentioned carbon material itself has a high transparency and can allow light to pass through. The reduced metal layer 12 includes nano-metal particles, which can be but not limited to one or more of gold (Au), silver (Ag), copper (Cu), platinum (Pt).
[0062] The free electrons in the carbon material layer 11 can transfer electrons in the conjugated structure of the carbon material layer 11 , and the free electrons outside the nano-metal particles of the reducing metal layer 12 can form an electron cloud for electron transfer, thereby making the transparent inorganic filler 10 have improved conductivity.
[0063] In some embodiments, the thickness of the transparent inorganic filler 10 is 5 nm to 10 nm. At a thickness of 5 nm to 10 nm, most of the light energy penetrates the material (only a small part is reflected and refracted), thereby ensuring that the inorganic filler has a transparent property.
[0064] In some embodiments, the thickness of the carbon material layer 11 is 0.4 nm to 1 nm, and the thickness of the reduced metal layer 12 is 2.5 nm to 4.5 nm. In this way, the total thickness of the transparent inorganic filler 10 can be ensured to be within the range of 5 nm to 10 nm, thereby ensuring that the inorganic filler has a transparent property, and the transparent inorganic filler 10 can also be ensured to have an improved conductivity.
[0065] When the carbon material layer 11 is a sheet of graphene oxide or reduced graphene, the thickness of the carbon material layer 11 refers to the thickness of a single sheet, and the thickness of the reduced metal layer 12 refers to the thickness of a single layer of the reduced metal layer 12 coated on the upper surface (or lower surface) of the graphene oxide or reduced graphene. When the carbon material layer 11 is a tubular carbon nanotube, the thickness of the carbon material layer 11 refers to the average thickness of the tube wall, and the thickness of the reduced metal layer 12 refers to the thickness of a single layer of the reduced metal layer 12 coated on the inner wall or outer wall of the tube.
[0066] In some embodiments, such as Figure 2 As shown, when the carbon material layer 11 is graphene oxide or reduced graphene, the transparent inorganic filler 10 is in the form of a sheet. The length of the sheet-shaped transparent inorganic filler 10 is 10 μm to 70 μm, and the width is 10 μm to 70 μm.
[0067] See also Figure 4 and Figure 5 In a third aspect, the present application provides a transparent conductive ink 20. In parts by weight, the transparent conductive ink 20 includes 5 to 15 parts of a transparent inorganic filler, 15 to 25 parts of a connector, 0 to 5 parts of an auxiliary agent, and 50 to 70 parts of a solvent. Figure 4 In the embodiment, the carbon material in the transparent inorganic filler 10 is flaky graphene oxide or reduced graphene. Figure 5 In the embodiment, the carbon material in the transparent inorganic filler 10 is a tubular carbon nanotube. The carbon nanotube described in the present application is an oxygen-containing functional group carbon nanotube, that is, the graphene sidewall of the carbon nanotube is introduced with an oxygen-containing functional group.
[0068] The connector, the additive and the solvent can form a polymer colloid 21, and the transparent inorganic filler 10 can be evenly dispersed in the polymer colloid 21, thereby forming a transparent conductive ink 20. The transparent conductive ink 20 described in the present application is a pressure-sensitive ink, which can be set on an insulating substrate by printing and cured by light. The cured transparent conductive ink 20 can be electrically connected to the circuit board through the conductive material, thereby forming a pressure sensor structure.
[0069] In some embodiments, the linker is a copolymer of ethylene, acrylic acid, and methacrylic acid. In other embodiments, the linker is polyvinyl alcohol (PVA).
[0070] In some embodiments, the additives include photoinitiators, leveling agents, and defoaming agents.
[0071] Further, the photoinitiator may be a free radical photoinitiator or a cationic photoinitiator. The free radical photoinitiator may be, but is not limited to, one or more of 1-hydroxycyclohexylphenyl ketone (photoinitiator 184), 2-phenylbenzyl-2-dimethylamine-1-(4-morpholinobenzylphenyl)butanone (photoinitiator 369), 2-isopropylthioxanthone (ITX), 2-methyl-1-(4-methylthiophenyl)-2-morpholino-1-propanone (photoinitiator 907), diphenyl-(2,4,6-trimethylbenzoyl)phosphine oxide (TPO), 2,4-diethylthioxanthone (DETX) and phenylbis(2,4,6-trimethylbenzoyl)phosphine oxide (photoinitiator 819). The cationic photoinitiator may be, but is not limited to, one or more of bis-2,6-difluoro-3-pyrrolophenyl titanocene (photoinitiator 784), sulfonium hexafluoroantimonate (photoinitiator 320), diphenyl-(4-phenylthio)phenylsulfonium hexafluorophosphate (photoinitiator UNI-6992) and η6-isopropylferrocenium hexafluorophosphate (photoinitiator 261).
[0072] Furthermore, the leveling agent may be a silicone system leveling agent, and the defoaming agent may be a silicone defoaming agent and a polyether defoaming agent.
[0073] In some embodiments, the solvent may be, but is not limited to, one or more of ethylene glycol butyl ether and aromatic hydrocarbon solvents.
[0074] The transparent conductive ink described in the present application has oxygen-containing groups in the carbon material of the transparent inorganic filler, which can generate hydrogen bonds in the polymer colloid and have better dispersibility, so it is not easy to agglomerate. In addition, the cross-sectional area of the reduced metal layer on the surface of the transparent inorganic filler is large and has a lower resistance, so that the conductivity of the transparent conductive ink is higher. In addition, the use of the transparent inorganic filler can make the conductive graphite transparent.
[0075] The transparent conductive ink of the present application will be further described below in conjunction with specific embodiments and comparative examples.
[0076] Example 1
[0077] In the transparent conductive ink of Example 1, the material selection and content of each component are shown in Table 1.
[0078] Table 1
[0079]
[0080] Comparative Example 1
[0081] The difference between Comparative Example 1 and Example 1 is that the inorganic filler is graphite. The rest is the same as Example 1 and will not be described again.
[0082] The transparent conductive ink of Example 1 and the conductive ink of Comparative Example 1 were observed under a transmission electron microscope, and the obtained electron microscope images were as follows: Figure 6 and Figure 7 As shown. Figure 6 As shown, in the transparent conductive ink of Example 1 of the present application, the transparent inorganic filler can be well dispersed in the polymer colloid. However, in the conductive ink of Comparative Example 1, the graphite is prone to agglomeration in the polymer colloid (e.g. Figure 7 The dispersion is poor.
[0083] See also Figure 8 In a fourth aspect, the present application provides a flexible sensor structure 100. The flexible sensor structure 100 includes a transparent conductive ink 20, a circuit substrate 30, a transparent conductive film 40 and a polyethylene terephthalate (PET) film 50.
[0084] The circuit substrate 30 includes a substrate layer 31 and a circuit layer disposed on the surface of the substrate layer 31. In this embodiment, the circuit layers 32 and 33 are disposed on two opposite surfaces of the substrate layer 31, respectively. In other embodiments, the circuit substrate 30 may also have more than three circuit layers 32. The circuit layers 32 may be electrically connected through a conductive structure 34. In this embodiment, the conductive structure 34 is a copper column, which electrically connects the two circuit layers 32 and 33 on the upper and lower surfaces of the substrate layer 31. The circuit substrate 30 may be a flexible printed circuit (FPC).
[0085] The transparent conductive ink 20 is disposed on the surface of the substrate layer 31 and is spaced apart from the circuit layer 32. That is, a portion of the surface of the substrate layer 31 is exposed from the circuit layer 32, and the transparent conductive ink 20 is disposed on the surface of the substrate layer 31 exposed from the circuit layer 32. The transparent conductive ink 20 can be disposed on the surface of the substrate layer 31 by printing.
[0086] The transparent conductive film 40 covers the transparent conductive ink 20 and the circuit layer 32 located on the same side as the transparent conductive ink 20, and the transparent conductive ink 20 and the circuit layer 32 are electrically connected through the transparent conductive ink 20. The transparent conductive film 40 can completely cover the transparent conductive ink 20 and the circuit layer 32, and can also cover part of the surface of the substrate layer 31 where the transparent conductive ink 20 is located. The transparent conductive film 40 can be poly (3,4-ethylenedioxythiophene-polystyrene sulfonic acid) (PEDOT / PSS), and PEDOT / PSS has excellent properties such as high conductivity, good light transmittance and easy processing.
[0087] The polyethylene terephthalate film 50 covers the transparent conductive film 40 and may also cover the surface of the base material layer 31 exposed from the transparent conductive film 40 .
[0088] In some embodiments, such as Figure 8As shown, the flexible sensor structure 100 further includes a cover film 60 . The cover film 60 is disposed on the surface of the circuit layer 33 (located on the other surface of the substrate layer 31 , opposite to the circuit layer 32 ) facing away from the substrate layer 31 to protect the circuit layer 33 .
[0089] The present application reduces nano-metal particles on the surface of a carbon material (graphene oxide, reduced graphene or carbon nanotubes) so that the surface of the carbon material is coated with a reduced metal layer. Since the free electrons in the carbon material can transfer electrons in the conjugated structure of the carbon material, the free electrons outside the nano-metal particles (reduced metal layer) can form an electron cloud for electron transfer, so that the prepared transparent inorganic filler has improved conductivity. In addition, the reduced metal layer on the surface of the transparent inorganic filler has a large cross-sectional area and a lower resistance, which further improves the conductivity of the transparent conductive ink. In addition, since the carbon material in the transparent inorganic filler contains oxygen-containing groups, the oxygen-containing groups can produce hydrogen bonds in the polymer colloid and have better dispersibility, so the transparent conductive ink of the present application is not prone to filler agglomeration problems.
[0090] The above descriptions are some specific implementations of the present application, but they are not limited to these implementations in actual application. For ordinary technicians in this field, other variations and changes made according to the technical concept of the present application should all fall within the protection scope of the present application.
Claims
1. A method for preparing a transparent inorganic filler, characterized in that: The preparation method comprises the following steps: Mixing and oscillating a carbon material with deionized water to prepare a carbon material solution; wherein the carbon material includes graphene oxide, reduced graphene or carbon nanotubes; The metal solution, the reducing agent solution and the carbon material solution are mixed and shaken to obtain a mixed solution; wherein the metal solution includes one or more of a silver nitrate solution, a tetrachloroauric acid solution, a copper sulfate solution, and a platinum chloride solution, and the reducing agent solution includes one or more of a hydrated hydrazine solution, an ammonium chloride solution, and a L-arginine solution; The mixed solution is periodically irradiated, wherein in each period, the irradiation frequency is 2.05 GHz to 2.95 GHz, the irradiation power is 800 W to 1000 W, the irradiation time is 45 to 50 seconds, and the rest time is 8 to 10 seconds; The irradiated mixed solution is centrifuged, washed and dried to obtain the transparent inorganic filler.
2. A transparent inorganic filler, characterized in that: The transparent inorganic filler is prepared by the preparation method as described in claim 1, and the transparent inorganic filler includes a carbon material layer and a reduced metal layer coating the carbon material layer, the carbon material layer includes graphene oxide, reduced graphene or carbon nanotubes, the reduced metal layer includes nano-metal particles, and the nano-metal particles include one or more of gold, silver, copper and platinum.
3. The transparent inorganic filler according to claim 2, characterized in that The thickness of the transparent inorganic filler is 5nm-10nm.
4. The transparent inorganic filler according to claim 3, characterized in that The thickness of the carbon material layer is 0.4 nm to 1 nm, and the thickness of the reduced metal layer is 2.5 nm to 4.5 nm.
5. The transparent inorganic filler according to claim 2, characterized in that: When the carbon material layer is graphene oxide or reduced graphene, the transparent inorganic filler is in the form of a sheet, and the length of the sheet-shaped transparent inorganic filler is 10 μm to 70 μm, and the width is 10 μm to 70 μm.
6. A transparent conductive ink, characterized in that: It includes the following components by weight: Wherein, the transparent inorganic filler is the transparent inorganic filler as claimed in any one of claims 2 to 5.
7. The transparent conductive ink according to claim 6, characterized in that: The linking agent includes copolymers of ethylene, acrylic acid, methacrylic acid or polyvinyl alcohol.
8. The transparent conductive ink according to claim 6, characterized in that: The auxiliary agents include photoinitiators, leveling agents and defoamers.
9. The transparent conductive ink according to claim 6, characterized in that: The solvent includes one or more of ethylene glycol butyl ether and aromatic hydrocarbon solvents.
10. A flexible sensor structure, characterized in that: include: A circuit substrate, the circuit substrate comprising a base material layer and a circuit layer arranged on a surface of the base material layer; The transparent conductive ink according to any one of claims 6 to 9, wherein the transparent conductive ink is disposed on the surface of the substrate layer and is spaced apart from the circuit layer; A transparent conductive film, the transparent conductive film covers the transparent conductive ink and the circuit layer, and electrically connects the transparent conductive ink and the circuit layer; and A polyethylene terephthalate film covers the transparent conductive film.